COMPARISON OF CASE-BASED LEARNING AND TRADITIONAL TEACHING TO EVALUATE LEARNING AND ACADEMIC OUTCOME OF FIRST-YEAR MBBS STUDENTS IN BIOCHEMISTRY CURRICULUM - BORGAONKAR, KAVINDRA; PATIL, RANJIT (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Competency-based medical education (CBME) is an outcome-based teaching method in which gain the knowledge of competencies for early clinical exposure. Case-based learning (CBL) is one of the approaches of CBME which makes learning more effective and interesting. In this backdrop, the present study was conducted to compare the outcome of CBL and the traditional method of teaching in the biochemistry curriculum. Methods: This cross-sectional study was conducted on 130 MBBS 1st year students and was divided into two groups, Group A (n=65) was allocated to CBL, and Group B (n=65) underwent a traditional teaching module. The pre- and post-test scores were compared between the groups and p<0.05 was considered significant. Results: The students were exposed to two lectures and for lecture 1 the post-test scores were significantly higher in CBL as compared traditional learning module (55.42±10.72 vs. 51.32±9.43; p=0.02). Similarly in lecture 2, the post-test scores were significantly higher in CBL as compared traditional learning module (58.87±10.76 vs. 53.12±8.28; p=0.01). Conclusion: CBL is a remarkable and efficient method for teaching biochemistry and it was positively perceived by students.